2021
DOI: 10.3390/vetsci8100233
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal and Piglet Low Protein Diet and Their Interaction on the Porcine Liver Transcriptome around the Time of Weaning

Abstract: Maternal diet during early gestation affects offspring phenotype, but it is unclear whether maternal diet during late gestation influences piglet metabolism. We evaluated the impact of two dietary protein levels in sow late gestation diet and piglet nursery diet on piglet metabolism. Diets met or exceeded the crude protein and amino acid requirements. Sows received either 12% (Lower, L) or 17% (Higher, H) crude protein (CP) during the last five weeks of gestation, and piglets received 16.5% (L) or 21% (H) CP f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(73 reference statements)
1
2
0
Order By: Relevance
“…The mean value of the rate of diarrhoea was 6.2% lower in the PHO group. Previous findings of Hăbeanu et al [ 8 ] have shown lowering (better) faecal consistency scores by limiting protein in the nursery diet which is consistent with more recent results from Kroeskea et al [ 63 , 64 ]. Oil derived from vegetable feedstuffs such as hemp seed, linseed, or algae is generally high in n-3 PUFA but weak in EPA and DHA, which have a higher bioactivity.…”
Section: Discussionsupporting
confidence: 88%
“…The mean value of the rate of diarrhoea was 6.2% lower in the PHO group. Previous findings of Hăbeanu et al [ 8 ] have shown lowering (better) faecal consistency scores by limiting protein in the nursery diet which is consistent with more recent results from Kroeskea et al [ 63 , 64 ]. Oil derived from vegetable feedstuffs such as hemp seed, linseed, or algae is generally high in n-3 PUFA but weak in EPA and DHA, which have a higher bioactivity.…”
Section: Discussionsupporting
confidence: 88%
“…For longer transcripts with many isoforms or non-poly(A) transcripts, traditional RNA-Seq may be more appropriate. To date, QuantSeq has been deployed in transcriptomic studies of multiple livestock species, including cattle ( Pascottini et al, 2021 ; Beak and Baik, 2022 ; Busato et al, 2022 ; Pedroza et al, 2022 ), sheep ( Kubik et al, 2018 ), chicken ( Ibrahim et al, 2021 ) and pigs ( Dong et al, 2018 ; Kroeske et al, 2021 ; Schroyen et al, 2021 ; Kramer et al, 2022 ).…”
Section: Additional Discussion Pointsmentioning
confidence: 99%
“…National Research Council (NRC) [3] recommends 12.9% CP in gestation diets for gilts (average 125 kg of body weight [BW]), but the CP requirement of NRC in 2012 [4] decreased by 2% to 4% compared to that of NRC in 1998 [3]. Many recent reports have been concerned about the decrease in dietary CP levels in the swine diet [5][6][7]. Moreover, as experimental results begin to accumulate, the application of low-protein diets in swine nutrition could be vigorously implemented in pig production to solve the problem of protein feed resource shortages and to alleviate environmental issues [8].…”
Section: Introductionmentioning
confidence: 99%